Next stop: Language. The ‘FOXP2’ gene’s journey through time - Adriana Schatton; Constance Scharff (Mètode Science Studies Journal: Annual Review)
How did humans evolve language? The fossil record does not yield enough evidence to reconstruct its evolution and animals do not talk. But as the neural and molecular substrates of language are uncovered, their genesis and function can be addressed comparatively in other species. FOXP2 is such a case – a gene with a strong link to language that is also essential for learning in mice, birds and even flies. Comparing the role FOXP2 plays in humans and other animals is starting to reveal common principles that may have provided building blocks for language evolution.